Preparation and Properties of Finely Dispersed Foodstuffs from Raw Vegetable Materials - Burushkina, T.N.; Ratushniak, V.V.; Kolychev, V.I.; Prepodobnyi, V.M.; Plotnikov, Yu.A. (Science and Innovation, 2024)
A low-waste technique for preparing liquid and paste-like finely dispersed emulsion and suspension systems of whole leguminous and cereal seeds (soya, lupine, amaranth, oats, wheat, and buckwheat) has been developed. These systems have almost complete set of nutrients, biologically active substances, and minerals of the original plants. They have an aggregative stability of 5–15 days or more without the use of stabilizers and emulsifiers.